A study of literacy instructional strategies used by primary teachers - Thalia Simbih Gilingan (2014)
In this study, I am attempt to discover the instructional strategies used by 60 primary teachers in Sabah. In answering the plea from Piller and Skillings (2005) for a replication of a study that has been conducted in New Dehli, such research has been conducted within the Sabah context. The theoretical framework for this study draws from Collier's Conceptual Model, Acquiring a Second Language, explaining the complex interacting factors students experience when acquiring a second language, and the work of Dorothy Strickland outlining effective literacy instruction. Explanatory case studies as the backbone for this research will be used. In this research, Case - based method is being used as a tool for collecting the data then, analyse the obtained data by using thematic analysis technique to Emerging from the data are twenty two effective teaching strategies that teachers of English learners can add to their repertoire.